2010
DOI: 10.1289/ehp.0901149
|View full text |Cite
|
Sign up to set email alerts
|

Silver Impairs Neurodevelopment: Studies in PC12 Cells

Abstract: BackgroundExposure to silver is increasing because of silver nanoparticles in consumer products.Objectives and methodsMany biological effects of silver entail actions of Ag+ (monovalent silver ions), so we used neuronotypic PC12 cells to evaluate the potential for silver to act as a developmental neurotoxicant, using chlorpyrifos (CPF), a pesticide known to evoke developmental neurotoxicity, as a positive control for comparison.ResultsIn undifferentiated cells, a 1-hr exposure to 10 μM Ag+ inhibited DNA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 35 publications
4
76
1
Order By: Relevance
“…These broad applications, however, increase human exposure and thus the potential risk related to their short-and long-term toxicity [7] . The health effects of this material have not been well characterized even though the toxicity of nanosilver has been demonstrated in vitro models [8] .…”
Section: Introductionmentioning
confidence: 99%
“…These broad applications, however, increase human exposure and thus the potential risk related to their short-and long-term toxicity [7] . The health effects of this material have not been well characterized even though the toxicity of nanosilver has been demonstrated in vitro models [8] .…”
Section: Introductionmentioning
confidence: 99%
“…There is data that silver nanoparticles are more toxic than silver microparticles or ions [51][52][53]. Powers et al [53] have shown that silver nanoparticles have the potential to evoke developmental neurotoxicity even more potently than known neurotoxicants.…”
Section: Snark Kinase As a Stress Sensor And Sensitive Marker Of Silvmentioning
confidence: 99%
“…Powers et al [53] have shown that silver nanoparticles have the potential to evoke developmental neurotoxicity even more potently than known neurotoxicants. Silver ions inhibited replication and increased cell death in undifferentiated cells, and selectively impaired neurite formation.…”
Section: Snark Kinase As a Stress Sensor And Sensitive Marker Of Silvmentioning
confidence: 99%
“…The toxicity of silver nanoparticles (Ag NP) has been documented in a large number of in vitro studies using a number of cell lines including but not limited to human hepatoma cells , PC12 neuronal cells (Powers et al, 2010), BRL3A rat liver cells, germline stem cells (Braydich-Stolle et al, 2005), human lung fibroblasts, and gliablastoma cells (AshaRani et al, 2009). However, a fewer number of in vivo studies using animal models has been conducted Ahamed et al, 2010b;Posgai et al, 2009;Kumari et al, 2009;Li et al, 2010;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%